Upaya Perlindungan dan Penegakan Hukum Terhadap Kelompok Rentan (Anak Korban Kekerasan Seksual) - Lukman Arif Asmanna; Mitro Subroto (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Write Children are potential, successors, and valuable assets as the next generation of the nation, so the quality and projection of the future of children must be considered because it will affect the life of the nation and state in the future. Every child has human rights that are regulated in the 1945 Constitution of the Republic of Indonesia and the United Nations Convention on the Rights of the Child. However, children have become a target for irresponsible individuals to satisfy their lust. Sexual violence against minors has an impact on the psychology and growth of children. The impact of sexual violence against children is exacerbated by the existence of a victim blaming culture that places the victim's position partly responsible for everything that happens to him. This study discusses efforts to protect and enforce the law against vulnerable groups of child victims of sexual violence. The research method used in this research is a literature study with a qualitative descriptive approach. A research method used to examine objects or other phenomena with actual conditions in the field to then create a systematic and accurate general picture.